EVALUASI KEBIJAKAN PROGRAM KELUARGA HARAPAN DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Jenni Novita; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Program Keluarga Harapan (PKH) is a conditional cash transfer program to accelerate poverty reduction. This family of hope program is a social protection program that provides cash assistance to Very Poor Households (RTSM) and for family members are required to carry out the requirements and conditions that have been set in the fields of education and healt. Program Keluarga Harapan in Tenayan Raya District is an area that has the highest beneficiary families in the city of Pekanbaru. With many poor families in this area, of course, it is necessary to collect data on poor families who deserve to receive the benefits of Program Keluarga Harapan (PKH) properly and correctly so that the program can be right on target. The purpose of this study was to find out how to evaluate the implementation of Program Keluarga Harapan in Tenayan Raya Subdistrict, Pekanbaru City and to determine the factors that influence this Family Hope Program. The theoretical concept used to William Dunn’s policy evaluation theory , namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. This study uses a purposive sampling technique with a qualitative research type, using a descriptive approach and the required data, both primary and secondary data, were obtained by interview documentation technique for further analysis. The results of this study indicate that the implementation of Program Keluarga Harapan in the Tenayan Raya Subdistict, Pekanbaru City has not run optimally. As for the factors that infuence the process of this family of hope program is the implementation of the program (SDM), the small nominal, and the target of the program. Keywords: Evaluation, Poverty, Program Keluarga Harapan